An Advanced Method of Collision Risk Assessment in terms of Encountering Ships. Issue 5 (January 2021) - Deng, Yuting; Zhang, Weibin; Feng, Xinyu
Abstract: In the risk management of maritime transportation, near-miss collisions by ships comprise a significant risk. Under the background of intelligent transportation, the emergence of technologies such as unmanned driving put forward higher requirements for maritime risk detection models. Previous studies have rarely been able to adaptively estimate the risk of near-miss collisions in different situations, especially for rare but existing encounters. Given this, this paper aims to improve the Vessel collision risk operator (VCRO) and proposes an exponential model of the safety distance in terms of the imbalance of risk assessment in the case of ships meeting close to the safety zone. Then combining the two risk standards set in the ship collision risk operator, and considering the impact of relative speed and relative course on collision risk, the risk detection model is further improved. The simulation results show that the improved ship collision risk assessment model is more applicable and accurate for the detection of collision risk in the open sea.